O Judiciário e as instituições de repressão frente ao discurso de tolerância zero = The judiciary and the institutions of repression facing the zero tolerance media discourse - Quister, Ezequiel Schukes (Revista Eletrônica de Direito Penal e Política Criminal, 2023)
The objective of this article is to reflect on the discourse of "zero tolerance" and the impact generated on the performance of the judiciary and institutions of state repression. Estimates from the Criminal Police Department (DEPEN) show that the prison population in Brazil will reach 1.5 million people in 2025, justifying the debate in view of the increase in prison incarceration in the country. In this article, from the analytical-deductive method on the theoretical reflection on the literature referring to Criminal Law and Criminology, it is argued about the dissemination of the discourse of "zero tolerance" as the modus operandi of state authorities, receiving apology from the coverage sensationalist media and influencing the behavior of judges, courts, courts and the very institutions of state repression to the detriment, sometimes, of the protection of constitutional rights.